Shoot and root development in rice (Oryza sativa L.) genotypes during progressive drying in soils with varying moisture regimes (2012)
Rainfed lowland rice productivity is negatively affected by drought. Root plasticity is a key trait for plant adaptation, and an important consideration in breeding high-yielding rice suited to drought-prone environments. This study was conducted to characterize shoot and plastic root developmental responses of the parents of doubled-haploid lines (DHL), and identify the drought intensity that can induce greater differences in root plasticity between parents. Rice genotypes CT9993 (upland japonica) and IR62266 (lowland indica) were grown in greenhouse and subjected to continuously waterlogged (CWL) and transient waterlogged-to-droughted (W-D) conditions with different soil moisture contents (SMC). Under W-D, CT 9993 had progressive reductions in shoot biomass with decreasing SMC down to 20%, before it further reduced to 5% SMC. In contrast, IR62266 had progressive reductions in shoot biomass with decreasing SMC down to 15%. Furthermore, CT 9993 also maintained stomatal conductance and transpiration, unlike I62266, during the progressive drying. On the other hand, photosynthesis increased in IR62266 unlike in CT9993, which was maintained, thereby improving its water use efficiency under W-D down to 5% SMC. Compared with IR62266, CT993 under W-D at 10% SMC had higher ratio of nodal roots, almost equal proportion of root lengths among soil depths, and greater promotion of L-type lateral roots at deeper soil layer where moisture is relatively higher than at shallow soil layer. Under W-D, key traits for drought adaptations include greater root plasticity in terms of nodal root production and elongation, and branching in CT9993 and shoot response for improved photosynthesis in IR62266. Furthermore, the drought intensity at 10% SMC induced greater differences in root plastic development between parents during progressive soil drying.